2010
DOI: 10.1124/jpet.110.166421
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Plasma Cysteine/Cystine and GSH/GSSG Redox Potentials by Acetaminophen and Sulfur Amino Acid Insufficiency in Humans

Abstract: Variations in plasma sulfur amino acid (SAA) pools are associated with disease risks, but little information is available about the factors affecting plasma SAA pools. Drug metabolism by glutathione (GSH) and sulfate conjugation can, in principle, represent a quantitatively important burden on SAA supply. The present study was designed to determine whether therapeutic doses of acetaminophen (APAP) alter SAA metabolism in healthy human adults. A double-blind, crossover design incorporating four treatment period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…The increased excretion of dimethyl sulfone and methionine sulfoxide meant that oxidation of sulfur-containing compounds occurred, likely as a consequence of decreased antioxidant capacities of cysteine and GSH. This is supported by the observation that paracetamol treatment oxidized the plasma cysteine/ cystine redox potential in human (Mannery et al 2010). An increased oxidative stress could have clinical effect, since oxidative stress has been implicated in the pathogenesis of cancer, diabetes mellitus, atherosclerosis, neurodegenerative diseases, rheumatoid arthritis, ischemia/reperfusion injury, obstructive sleep apnea, other diseases, and also in senescence (Dröge 2002).…”
Section: Metabolic Effects Of Paracetamol Treatmentsupporting
confidence: 69%
See 2 more Smart Citations
“…The increased excretion of dimethyl sulfone and methionine sulfoxide meant that oxidation of sulfur-containing compounds occurred, likely as a consequence of decreased antioxidant capacities of cysteine and GSH. This is supported by the observation that paracetamol treatment oxidized the plasma cysteine/ cystine redox potential in human (Mannery et al 2010). An increased oxidative stress could have clinical effect, since oxidative stress has been implicated in the pathogenesis of cancer, diabetes mellitus, atherosclerosis, neurodegenerative diseases, rheumatoid arthritis, ischemia/reperfusion injury, obstructive sleep apnea, other diseases, and also in senescence (Dröge 2002).…”
Section: Metabolic Effects Of Paracetamol Treatmentsupporting
confidence: 69%
“…Kinetics measurements were not performed for ethical reasons: elderly subjects were suffering. In volunteers aged 18 to 40 years, baseline plasma cysteine, cystine, reduced and oxidized forms of GSH concentrations were unchanged after 2 day of paracetamol treatment at the dose of 1 g/day (Mannery et al 2010). Nevertheless, in the latter study some differences appeared significant at some time-points across the 12-h kinetics.…”
Section: Paracetamol Metabolism In Older Personsmentioning
confidence: 73%
See 1 more Smart Citation
“…We observed that an oxidized blood GSH E h was correlated with decreased blood SAH and plasma Hcys, which is consistent with an increase in Hcys flux through the transsulfuration pathway under oxidized intracellular conditions. 16 Although some studies have used plasma GSH E h as a marker of intracellular redox, 44,45 we did not observe significant correlations of Hcys or SAH with plasma GSH E h , which suggests that whole blood GSH E h might be a better indicator of the intracellular redox environment, at least within blood cells. However, an oxidized plasma GSH E h is thought to reflect oxidative stress in other tissues 46 or systemic oxidative stress 47 and is observed in aging, 48 obesity 49 and disease states such as asthma 50 and heart disease.…”
Section: Discussionmentioning
confidence: 56%
“…This can deplete cysteine stores (56,57). In addition, conjugation of acetaminophen to glutathione reduces its levels.…”
Section: Acetaminophen and Acquired 5-oxoprolinemia/ 5-oxoprolinuriamentioning
confidence: 99%